Diversity, Prevalence And Host Specificity Of Parasites In Freshwater Fish Population In Selected Reservoirs Of Perak River, Perak - Ibrahim, Ado Abdulmalik (2021)
Past and present studies have shown that there are numerous pathogenic diseases caused by parasites in fishes but many fish parasites remain to be identified. There was no information on the prevalence of protozoa and myxozoa parasitic fauna of the fishes in the reservoirs along the Perak River. Molecular identification provides an accurate method for the identification of parasites. The DNA sequence of fish parasites in reservoirs along the Perak River has not been studied before. This research has identified the fish parasites from April 2017 until March 2019 in Temengor, Bersia, Chenderoh reservoirs except for Kenering reservoir, Perak. Morphological and first molecular identification of some selected monogeneans were studied. The host-parasites interactions were then visualized by a bipartite graph, followed up by the analysis of the effects of fish parasites on the relative condition factor (Kn), and the relationship of parasites with the water temperature, pH, and dissolved oxygen (DO) of the reservoirs. A total of 276 individuals fishes were sampled from the reservoirs with 161 (58%) fishes individuals were presence with parasites. Seventeen fish species were presence with parasites out of the 25 species. Thirty-two species of fish parasites were identified in this study which include two species of protozoans, two species of myxozoa, 12 species of monogeneans, three species of digeneans, one species of cestode, four species of nematodes, three species of acanthocephalans and five species of crustaceans. Bolantidium sp., Henneguya sp. and Myxobulus sp. were new recorded parasites species in the reservoirs. Monogeans were the dominant parasites found in the fishes with Paradiplozoon barbi (17.39%) recorded the highest prevalence rate.